Amperometric determination of sulfide at a pre-oxidised nickel electrode in acidic media. - Giovanelli, D; Lawrence, N; Jiang, L; Jones, T; Compton, R (2003)
The electrochemical response of a pre-oxidised nickel electrode to increasing additions of sulfide has been examined and shown to produce a stripping-like voltammetric wave. A mechanism is described based on the formation of nickel sulfide at the electrode surface from a non-electroactive nickel oxide layer. The analytical utility of the approach has been examined and a linear range from 1 to 140 microM and a limit of detection of 0.8 microM is achievable, depending on the accumulation time.